Relaxant effect of Humulus lupulus extracts on isotonic rat's ileum contractions - Seyed Hassan Hejazian; Seyyed Majid Bagheri; Mohammad Hossein Dashti-R (Mashhad University of Medical Sciences, 2014)
O Objective: Many biological studies have been done to determine the activity of medicinal plants on gastrointestinal function. Since acetylcholine is the major transmitter involved in the gastrointestinal motility and there are some evidences regarding the cholinergic modulatory effect of hops extract, in the present study spasmolytic and antispasmodic action of hops(Humulus lupulus) on acetylcholine-induced contraction in isolated rat's ileum was evaluated. Material and Methods: In this study, pieces of isolated rat's ileum were mounted in the internal chamber of an organ bath which was filled with Tyrode's solution and tightly tied to the lever of an isotonic transducer. The contractile responses were recorded by using an oscillograph device. In the presence of normal saline and different concentrations of hops (0.1, 0.3, and 0.5 mg/ml), the amplitude of contractions induced by10-12 up to 10-2 M acetylcholine was determined. The spasmolytic action of the same extract concentrations was also examined on contraction induced by 10-4 acetylcholine. Results: Our findings indicate that hops extract reduces acetylcholine-induced contraction in all concentrations. The significant inhibitory effects of 0.1, 0.3, and 0.5 mg/ml hops extract on contraction induced by 10-3 M acetylcholine were 81.9, 77, and 29.3, respectively (p